Science, technology and society - Aldea, Kathryn Idrisha K.; Caronan, Hans Peter A.; Candido, Maria Blessilda O.
This book is one of the new general education courses in the CHED general education program. This module is based on outcome-based education curriculum which will help students develop their competencies and skills on communication, creativity, critical thinking, and problem solving. This module has been prepared for the students taking up STS subject good for one semester in the collegiate level. This module presents the general concepts and principles needed to study and understanding of science, technology and society. It is designed to enable students acknowledge and appreciate the scientific and technological development from the perspective of its historical developments up to 21st century and its impact to the humans and its society. The first part of the module includes a review of the history of science and technology from the prehistoric era all the way to today's advances in sciences and technology, how humans come up and invented this technology and how these technology help them improves ways of life. The historical survey is grounded on an understanding of basic science concepts and examine how these developments have affected the course of human society politically, economically, and socially. The second part of the course focuses on current issues arising from the application of science and technology, and how it affects human beings, its environment, and society in general. This module provides the students with the opportunity to read and learn more about science and technology considered in this study through lectures and activities.